Repositioning out-of-school learning : methodological challenges and possibilities for researching learning beyond school - Rose, Jo; Jay, Tim; Goodall, Janet; Smith, Laura Mazzoli; Todd, Liz (Emerald Publishing Limited, 2022)
Out-of-school learning spans varied formal and informal contexts and is hugely important for the lives of children. The need for time, flexibility, and agility in research within this field is highlighted throughout this multi-disciplinary edited volume, as each author reflects on how to make sense of the unknown and varied contexts in which out-of-school learning takes place. A range of different case studies discuss research methods used, challenges faced, and ways challenges were overcome in relation to out-of-school learning are presented, followed by a series of critical reflections. The case studies include a range of research foci and methods, from large-scale quantitative secondary data analysis, through interviews and workshops, to ethnographic and participatory methods. A series of shorter reflections drawing on all case studies consider the negotiation of the researcher role, building relationships, the ways knowledge is constructed, the role of place and power, keeping hold of messiness and complexity, ethical practice; and 'slow research'. The principles outlined in this volume are relevant for all research on learning, whenever and wherever it takes place - whether in school or out-of-school.
Includes index.
Keywords: Non-formal education -- Research.; Education, Non-Formal Education.; Education.; elektronické knihy; electronic books